2020
DOI: 10.1371/journal.pone.0226895
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory analysis of the potential for advanced diagnostic testing to reduce healthcare expenditures of patients hospitalized with meningitis or encephalitis

Abstract: Objective To estimate healthcare expenditures that could be impacted by advanced diagnostic testing for patients hospitalized with meningitis or encephalitis Methods Patients hospitalized with meningitis (N = 23,933) or encephalitis (N = 7,858) in the U.S. were identified in the 2010-2014 Truven Health MarketScan Commercial Claims and Encounters Database using ICD-9-CM diagnostic codes. The database included an average of 40.8 million commercially insured enrollees under age 65 per year. Clinical, demographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Previous studies in the United States 21 24 reported a shorter LOS in the hospital but more inpatient costs for patients with encephalitis of all causes than patients with AE in China in the present study. The average LOS in the hospital was 10.6–15.1 days.…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…Previous studies in the United States 21 24 reported a shorter LOS in the hospital but more inpatient costs for patients with encephalitis of all causes than patients with AE in China in the present study. The average LOS in the hospital was 10.6–15.1 days.…”
Section: Discussionsupporting
confidence: 50%
“…The reason for this difference may be as follows: patients in the LGI1/CASPR2 group had the shortest LOS in the hospital (median of 17.0 days, interquartile range [IQR] of 15.0-24.0), in agreement with a previous study indicating that LOS was significantly related to cost. 12 Previous studies in the United States [21][22][23][24] reported a shorter LOS in the hospital but more inpatient costs for patients with encephalitis of all causes than patients with AE in China in the present study. The average LOS in the hospital was 10.6-15.1 days.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…The variable turnaround times are not due as much to technical variations in the assays but rather to staffing levels and the degree of automation, both of which will increase as these tests become more common and routine 18 . A health-care economics modelling study based on actual insurance payments (as opposed to amounts charged) for hospitalized patients with meningitis or encephalitis found that an opportunity exists for mNGS testing to be cost-effective in patients who have undergone a neurosurgical procedure, who are critically ill, who are infected with HIV or who have had a solid organ transplant given that these patients have long lengths of stay and substantial costs throughout the length of their hospitalization 78 . For example, mNGS could decrease health-care costs by diagnosing a treatable disease, as seen in a patient who had a lung transplant and was diagnosed with hepatitis E virus meningoencephalitis and whose anti-viral treatment resolved their neuroinflammatory disease and probably also spared them a liver transplant 9 .…”
Section: Practical Considerations For Mngsmentioning
confidence: 99%